The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1143/jjap.34.6805
|View full text |Cite
|
Sign up to set email alerts
|

New Ultra-High-Frequency Plasma Source for Large-Scale Etching Processes

Abstract: A low temperature, uniform, high-density plasma is produced by an ultra-high-frequency (UHF) discharge using a new spokewise antenna. The plasma is uniform within ±5% over a diameter of 30 cm. The plasma density, 1×1011 cm-3, for low electron temperatures of 1.5-2.0 eV, is almost proportional to the UHF power even at a low UHF power. No magnetic field is needed to maintain a high-density plasma. Consequently, the plasma source is fairly simple and lightweight. The plasma source can accomplish a notch-free pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…[1][2][3][4][5][6][7] We have previously reported measurements of the absolute densities of Cl 2 , Cl, Cl 2 ϩ , Cl ϩ , and Ar ϩ in inductively coupled plasmas ͑ICPs͒ containing such mixtures; such measurements should be useful to investigations of the etch mechanism, rate, selectivity, and etched profile shapes. [8][9][10] Eddy et al have used a Langmuir probe to measure T e as a function of rf power and Ar fraction in Cl 2 -Ar electron cyclotron resonance discharges. The electron energy distribution function ͑EEDF͒ ͑and therefore T e ͒ can affect the undesirable etched profile anomalies, such as bowing and microtrenching, and electrical damage due to charge build-up and current flow, as have been observed in the etching of silicon device materials ͑e.g., Si and Al͒.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] We have previously reported measurements of the absolute densities of Cl 2 , Cl, Cl 2 ϩ , Cl ϩ , and Ar ϩ in inductively coupled plasmas ͑ICPs͒ containing such mixtures; such measurements should be useful to investigations of the etch mechanism, rate, selectivity, and etched profile shapes. [8][9][10] Eddy et al have used a Langmuir probe to measure T e as a function of rf power and Ar fraction in Cl 2 -Ar electron cyclotron resonance discharges. The electron energy distribution function ͑EEDF͒ ͑and therefore T e ͒ can affect the undesirable etched profile anomalies, such as bowing and microtrenching, and electrical damage due to charge build-up and current flow, as have been observed in the etching of silicon device materials ͑e.g., Si and Al͒.…”
Section: Introductionmentioning
confidence: 99%
“…The most prominent feature is the strong absorbance band at 1100-1400 cm Ϫ1 , attributable to all CF x (xϭ1,2,3) stretching modes. 6 And it has been reported that C 2 F 4 gas chemistries suppress charge-up damage during etching processes. The CvC vibration is normally observed at 1600 cm Ϫ1 in organic compounds when the C is backbonded to H, but it is typical for the CvC stretch to shift to higher frequencies when the H atoms are replaced by F atoms.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, various discharge sources for large-area processing have been proposed, including inductively coupled plasma sources with multiple inductive antennas 1 or with antennas that launch traveling waves, 2 ECR plasma sources with plane slotted antennas and permanent magnets, 3 modified magnetron-typed radio-frequency ͑rf͒ plasma sources, 4 or ultra-high-frequency ͑UHF͒ plasma sources with spokewise antennas. 5 Recently Kim et al has proposed a new antenna configuration to produce uniform large-area ICPs, 6 using the parallel LC-resonance of the antenna ͑Resonant ICP or RICP͒. The antenna of this system consists of segmented coils, which are connected in parallel and tuned with an external variable capacitor as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%